The Effects of Anisotropic Yield Functions on Plastic Behavior of 304 Stainless Steel - Sener, Bora; Yurci, Mehmet Emin (AMER SOC TESTING MATERIALS, 2018)
The effects of anisotropic yield functions on plastic behavior of 304 stainless steel were investigated in this study. Two yield functions were considered: Hill'48 and Barlat89. Uniaxial tensile tests were carried out 0 degrees, 45 degrees, and 90 degrees from the rolling direction to determine the mechanical properties of the material. The planar distributions of yield stress and the anisotropy coefficient were predicted using the yield models and compared with the experimental results. Subsequent yield surfaces of Hill'48 and Barlat89 were investigated and compared with each other. Deep drawing of a double bowl sink and its simulation were carried out in order to evaluate the prediction ability of the two functions under complex loading conditions. It has been observed that predicted results from Barlat89 criterion showed good agreement with experimental data.
Keywords: yield function; 304 stainless steel; anisotropy; finite element simulation; FORMABILITY PREDICTION; STRENGTH; Materials Science